Knowledge of students graduating from the undergraduate Nursing course on basic life support (Research, Society and Development, 2020)
The objective was to analyze the knowledge of students of the Nursing Graduation Course of a private Higher Education Institution in Belém, State of Pará, Brazil about Basic Life Support. This is a cross-sectional, descriptive, exploratory study, with a quantitative approach, carried out from September to October 2018. In the assessment of knowledge about Basic Life Support, on a scale of 0 to 100 points, it was found that the lowest score was 20.6 points and the highest was 90.4. The average was 63.5 points, with a standard deviation of 15.5. The median was 64 points, with an interquartile deviation of 20 points (54 to 74 points). It was evident that 62% of the students scored less than 70 points and 19% scored less than 50 points. The studied population has reduced and sometimes inadequate knowledge about cardiopulmonary arrest and cardiopulmonary resuscitation, which may compromise the care provided, causing damage to resuscitation and, consequently, contributing to the emergence and/or aggravation of sequelae, impacting the increase in morbidity and mortality. It was understood to be fundamental to the institution's training and evaluation, both theoretically and practically, as a way to optimize and consolidate knowledge even during academic training.